Pre-Service Teachers’ Perception of Autonomous Learners in the 21st Century - Nuraeni, Nuraeni; Anggraini, Ajeng (Institut Hindu Dharma Negeri Denpasar, 2020)
This study aims to investigate pre-service teachers’ perceptions of autonomous learners in the 21st century. By using the quantitative method in this study, the researcher distributed the questionnaire to 13 pre-service teachers in the 5th semester English education program at Ibn Khaldun University. There are 5 questions in the questionnaire related to this study. It intends to explore information related to how much pre-service teachers understand and what their perception of autonomous learners in the 21st century. The researcher distributed questionnaires to all participants through WhatsApp broadcast and all participants got the Google form link to answer all of the questions. Responses from participants regarding autonomous learners are processed by the researcher. Is that the results obtained that participants understand the concept of autonomous learners but the lack of application of autonomous learners in teaching and learning activities. The researchers in this study suggest that in the 21st century requires a deep understanding of autonomous learners by pre-service teachers to prepare the teaching-learning process in the class by using autonomous learners.